Digital Transformation Training for Village Community Groups in Efforts to Turn Sumberejo Village into a Smart Village - Yunas, Novy Setia; Wibowo, Dhimas Bagus Bimasena; Ratu, Jessica Gustriana; Novarani, Nabila; Putri, Pangestika Maharani; Mairisa, Puti Zanira; Muhammad, Aliyu Dahiru (Yayasan Pendidikan Islam Bustanul Ulum Mojokerto, 2024)
The rapid development of technology in the world which is beneficial for people's lives means it is necessary to master technology as time goes by. This training aims to enable students to provide ideas based on knowledge, to grow and accelerate movement in preparing future cadres and accelerate the achievement of a Smart Village in Sumberejo Village. There are several digital training provided, such as training on using editing applications, namely Canva and Filmora, training on creating and maintaining social media, namely village Instagram and YouTube, training on maintaining and optimizing village websites, and training on financial report management applications for BUMdes. This program was implemented well and smoothly because a regular socialization and training agenda had been implemented for village cadres according to their chosen interests. Regular training is needed for cadres to be able to master soft skills better, and of course, support from the village government is needed for cadres to facilitate the learning process so that it can be useful for village progress.